Who's counting? Legitimating measurement in the audit culture. Issue 3 (3rd May 2016) - Ocean, Jude; Skourdoumbis, Andrew
Abstract : What gives legitimacy to the numbers that constitute the measurement techniques of the audit culture? We argue that the audit culture's blind application of numbers to people as if there was no moral or ethical dimension to the calculation rests on a military discourse resident in mathematics. This argument is based on the genealogy presented in this paper, which uncovers a regime of measurement-by-number, sedimented as legitimate through an association with military power. We claim that this military measurement-by-number is a dubious technique of government on which the audit culture relies for its highly questionable authority.